Brain Damage in the Preterm Infant: Clinical Aspects and Recent Progress in the Prevention and Treatment - Xie, Yixuan; Yang, Yue; Yuan, Tianming (CNS & Neurological Disorders - Drug Targets, 2023)
Although the prevalence of brain injury and related neurodevelopmental disabilities resulting from preterm birth are major public health concerns, there are no definite neuroprotective strategies to prevent or reduce brain injury. The pattern of brain injury seen in preterm infants has evolved into more subtle lesions that are still essential to diagnose regarding neurodevelopmental outcomes. There is no specific effective method for the treatment of premature infant brain injury, and the focus of clinical treatment is still on prevention. Prevention of this injury requires insight into the pathogenesis, but many gaps exist in our understanding of how neonatal treatment procedures and medications impact cerebral hemodynamics and preterm brain injury. Many studies provide evidence about the prevention of premature infant brain injury, which is related to some drugs (such as erythropoietin, melatonin, mesenchymal stem cells, etc.). However, there are still some controversies about the quality of research and the effectiveness of therapy. This review aims to recapitulate the results of preclinical studies and provide an update on the latest developments around etiological pathways, prevention, and treatment.
Keywords: mesenchymal stem cell